A STUDY OF THE FOUR NOBLE TRUTHS IN DHAMMACAKKAPAVATTANA SUTTA - Hai Yen, Nguyen (International Journal For Research In Educational Studies, 2023)
More than two thousand and five hundred years ago, an enlightened person was born and found a way to free all beings from suffering; that is Buddha Gotama. Although he was born a prince, he could see the pain and suffering sentient beings had to endure. Therefore, he sacrificed his happiness to help all sentient beings free from suffering. After attaining enlightenment, he saw the true nature of life, its cause, its cessation, and the way to that cessation. This is also all that the Buddha wanted sentient beings to see and practice. In this article, the writer will analyze the four truths taught by the Buddha in his first sutta